2006
DOI: 10.1158/0008-5472.can-05-2919
|View full text |Cite
|
Sign up to set email alerts
|

Matrix Metalloproteinases Play an Active Role in Wnt1-Induced Mammary Tumorigenesis

Abstract: The Wnt signaling transduction pathway plays a critical role in the pathogenesis of several murine and human epithelial cancers. Here, we have used mouse mammary tumor virus (MMTV)-Wnt1 transgenic mice, which develop spontaneous mammary adenocarcinoma, to examine whether matrix metalloproteinases (MMPs)-a family of extracellular proteases implicated in multiple steps of cancer progressioncontributed to Wnt1-induced tumorigenesis. An analysis of the expression of several MMPs by RT-PCR and in situ hybridization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(57 citation statements)
references
References 51 publications
0
57
0
Order By: Relevance
“…Accordingly, we previously reported an upregulation of the expression of several MMPs in the mammary tumors of MMTV/Wnt1 transgenic mice. We also demonstrated that when crossed with mice overexpressing Tissue Inhibitor of Metalloproteinases (TIMP)-2 under the same MMTV promoter, double transgenic mice develop fewer tumors with an increased latency, 29 suggesting therefore that MMPs may also play a contributory role in Wnt1-mediated malignant transformation. Here we have used Wnt1 overexpressing C57MG mouse mammary epithelial cells to demonstrate that MMPs are both targets and contributors to Wnt-induced EMT.…”
Section: Stromelysin-1 (Mmp-3) Is a Target And A Regulator Of Wnt1-inmentioning
confidence: 90%
See 2 more Smart Citations
“…Accordingly, we previously reported an upregulation of the expression of several MMPs in the mammary tumors of MMTV/Wnt1 transgenic mice. We also demonstrated that when crossed with mice overexpressing Tissue Inhibitor of Metalloproteinases (TIMP)-2 under the same MMTV promoter, double transgenic mice develop fewer tumors with an increased latency, 29 suggesting therefore that MMPs may also play a contributory role in Wnt1-mediated malignant transformation. Here we have used Wnt1 overexpressing C57MG mouse mammary epithelial cells to demonstrate that MMPs are both targets and contributors to Wnt-induced EMT.…”
Section: Stromelysin-1 (Mmp-3) Is a Target And A Regulator Of Wnt1-inmentioning
confidence: 90%
“…42 We previously reported that overexpression of TIMP-2 in the mammary glands of MMTV-Wnt1 mice inhibited tumor formation suggesting that MMP inhibition could prevent or delay malignant transformation of epithelial cells. 29 Here, using the same MMTV-Wnt1 transgenic tumor model, we examined the effect of a preventive treatment using low dose (50 mg/kg) of a small MMP inhibitor, AG3340, that was administered twice a week. In previous experiments we had used higher doses (100 mg/kg) of the inhibitor administered twice daily by gastric gavage.…”
Section: Preventive Treatment With Mmp Inhibitor Prevents and Delays mentioning
confidence: 99%
See 1 more Smart Citation
“…Various molecular events, which were involved in aberrant remodeling in this model of mammary tumorigenesis included extracellular matrix modulators (Matrix Metalloproteinases (MMP)/ Tissue Inhibitors of Matrix Metallo-proteinases (TIMP) [80], soluble peptide factors/co-receptors Fgf8 [81], Lrp6 [82], and cell surface proteins (Syndecan-1) [83]. Moreover, about 50 molecules were identified as remodeling factors, and the effect of individual factors on such remodeling events needed to be assessed.…”
Section: Microenvironment Remodeling Of Stem Cells Into Cancer Stem Cmentioning
confidence: 99%
“…Overexpression of Wnt1 in the virgin mammary gland that activates a canonical Wnt/b-catenin/Lef-1 signaling pathway can produce precocious alveolar hyperplasia and ductal hyper-branching, which eventually results in the development of mammary adenocarcinomas [16]. An increase in the expression of MMP2, MMP3 and MMP9 occurs in the mammary stroma of Wnt1 transgenic mice whereas MMP13 is expressed by the transformed mammary epithelial cells (MECs), suggesting that additional MMPs other than MMP2 and MMP3 can contribute to tumor progression after sustained activation of a Wnt/b-catenindependent pathway [17]. Finally, during pregnancy, lobuloalveolar development is regulated by progesterone and prolactin.…”
Section: Reviewmentioning
confidence: 99%